Characterization of oil injected screw compressors and air/oil separators at realistic operating pressures. Issue 11 (2nd November 2019) - Kaiser, Simon; Gugelfuß, Anne; Gyurkovich, Alexander; Rupp, Marcus; Mehring, Carsten; Piesche, Manfred
Abstract: An experimental setup to determine the particle size distribution (PSD) of a pressurized oil aerosol ( p < 10 bar ) was validated. The combination of optical particle counter (OPC) and scanning mobility particle sizer (SMPS) measurements allowed for the evaluation of PSDs in the size range 40 nm < d p < 3 μm . The raw gas oil emissions of two oil injected screw compressors were determined and compared to a test aerosol generated by a Laskin Nozzle aerosol generator. While the screw compressors showed considerable differences in gravimetric oil load, the normalized PSDs of both compressors were found to be similar, exhibiting main mass fractions in the particle size range between 0.1 and 2 µm. The influence of operating conditions on the fractional separation efficiency of fibrous oil mist filters was also studied in this work using a conventional air/oil separator filter. An increase of either pressure, temperature, filter face velocity or oil loading rate led to a deterioration of separation efficiency emphasizing the need for filter testing under realistic operating conditions. Copyright © 2019 American Association for Aerosol Research